Sacroiliac Joint Involvement in von Recklinghausen Neurofibromatosis - Olfa SAIDANE; Ines CHERIF; Rawdha TEKAYA; Ines MAHMOUD; Leila ABDELMOULA (Archives of Rheumatology, 2017)
Neurofibromatosis (NF) type I is a genetic disorder caused by a mutation of the NF type I gene. This disease is associated with a variety of skeletal manifestations. In this article, we report a 33-year-old female patient with a known history of von Recklinghausen’s disease and inflammatory right buttock pain. Diagnostic imaging pointed out unilateral sacroiliitis possibly of a septic origin. Sacroiliac biopsy showed histological patterns consistent with NF. This case report summarizes an exceptional localization of NF mimicking the imaging of infectious sacroiliitis.